Comparing Traditional and Economic Performance Measures for Creating Shareholder’s Value: a Perspective from Malaysia - Panigrahi, Shrikant; Yuserrie, Zainuddin; Noor Azlinna, Azizan (Human Resource Management Academic Research Society, 2014)
This study investigates the importance of economic value added for the shareholders wealth maximization. Economic value added (EVA) is a value based performance measurement tool that inclines the agency conflict issues between managers and shareholders. Using a sample of 28 construction public listed companies in main board of Bursa Malaysia and using panel data with fixed effects during the period of 2003 to 2012, the findings of the study revealed that there is a positive and significant relationship between EVA and shareholder’s wealth maximization. The more the managers produce EVA, the more shareholders’ wealth maximization will be created. The finding shows significant support for EVA, but EVA was not reported by the companies and is not been used by investors for their investment decisions. Thus it is recommended for the managers to focus more attention to the criteria of EVA in evaluating shareholder’s value.